Essays Connecting Australian Dwelling Price Growth and Subjective Wellbeing to Within-City Income and Wealth Differentials - Phelps, Christopher Vincent (Curtin University, 2021)
This thesis comprises three independent research essays that address knowledge gaps in the Australian literature surrounding the response of housing prices and individual wellbeing to residential segregation within Australian cities.